Hidden in Plain Sight: Electromechanical Window Negativity in Congenital Long QT Syndrome - Toby Paterson; Roy Sanders; Vivetha Pooranachandran (Clinical Case Reports, 2026)
ABSTRACT Risk stratification in congenital long QT syndrome (LQTS) continues to rely heavily on genotype and QTc duration, despite their limited ability to identify individuals at highest arrhythmic risk. The electromechanical window (EMW) is a validated marker of malignant arrhythmia susceptibility, yet its presence within routine echocardiographic imaging has not been recognized. We report a 19‐year‐old woman with KCNH2 ‐related LQTS who experienced recurrent syncope triggered by abrupt auditory stimuli, with ambulatory monitoring revealing self‐terminating torsades de pointes up to 273 beats/min. Although cardiac magnetic resonance and standard echocardiography showed normal structure, retrospective analysis of archived routine cine loops revealed marked EMW negativity (mean −97.5 ms), measurable directly from standard imaging without specialized acquisition. Retrospective analysis demonstrated that marked EMW negativity was measurable from routine echocardiographic images acquired before the diagnosis was established. This case suggests that EMW negativity may be silently present in many previously imaged LQTS patients and recoverable retrospectively from existing echocardiographic datasets.